How Interpersonal Justice Shapes Legitimacy Perceptions: The Role of Interpersonal Justice Trajectories and Current Experience - Liang, Juan; Xu, Bibo (Frontiers in Psychology, 2020)
Despite a growing body of research on the relationship between justice and perceptions of an authority’s legitimacy, few studies have addressed the effects of changes in justice on perceived legitimacy. In the present study, we tested a dynamic model emphasizing the interactive influences of both interpersonal justice trajectories and current experience predicting perceived legitimacy. We tested the trajectory of interpersonal justice over time as a predictor of perceived legitimacy (Study 1) and the current experience of justice as a moderator of this link (Study 2). In Study 1 participants were randomly assigned to receive either improving or declining feedback from an anonymous tutor over the course of four days. Results showed that participants with an improving trajectory perceived the authority to have higher legitimacy. In Study 2 participants rated the tutor’s fairness on 3 consecutive weeks, which were used to identify naturally interpersonal trajectories; we then manipulated the current interpersonal justice experience in the fourth week. Results showed that the trajectory effect was significant when the current experience was just, but not when it was unjust.